The genome of Mesobuthus martensii reveals a unique adaptation model of arthropods - Cao, Zhijian; Yu, Yao; Wu, Yingliang; Hao, Pei; Di, Zhiyong; He, Yawen; Chen, Zongyun; Yang, Weishan; Shen, Zhiyong; He, Xiaohua; Sheng, Jia; Xu, Xiaobo; et al. (Nature communications, 2013)
Representing a basal branch of arachnids, scorpions are known as ‘living fossils’ that maintain an ancient anatomy and are adapted to have survived extreme climate changes. Here we report the genome sequence of Mesobuthus martensii , containing 32,016 protein-coding genes, the most among sequenced arthropods. Although M. martensii appears to evolve conservatively, it has a greater gene family turnover than the insects that have undergone diverse morphological and physiological changes, suggesting the decoupling of the molecular and morphological evolution in scorpions. Underlying the long-term adaptation of scorpions is the expansion of the gene families enriched in basic metabolic pathways, signalling pathways, neurotoxins and cytochrome P450, and the different dynamics of expansion between the shared and the scorpion lineage-specific gene families. Genomic and transcriptomic analyses further illustrate the important genetic features associated with prey, nocturnal behaviour, feeding and detoxification. The M. martensii genome reveals a unique adaptation model of arthropods, offering new insights into the genetic bases of the living fossils. Scorpions have maintained the primary anatomical features of their Paleozoic arthropod ancestors. Here, the authors report the genome sequence of Mesobuthus martensii and highlight evidence of genetic and morphological evolution that represents a unique adaptation model of arthropods.